Trichosporon species isolated from scald burn wound in an immunocompetent adult: a case report from Southern Assam - Bhattacharjee, Barnamoy; Chanda, Debadatta D.; Chakravarty, Atanu (International Journal of Research in Medical Sciences, 2021)
There are quite a good number of case reports on fungal infection in burn wounds in addition to the conventionally notorious bacterial infections in immune-compromised burn trauma patients leading to protracted course of morbidity and higher chances of mortality due to delay in diagnosis. The incidence of fungal infection in burn patients has been increasing with paradigm shift of causal fungus over last 2 decades from Candida albicans and molds to non-albicans Candida, Trichosporon species and other yeast like fungus. But there are rarely few cases of invasive Trichosporon infection in scald burn wounds in immunocompetent individuals. We therefore report a case of Trichosporon species isolation from a scald burn ulcer of an immunocompetent young male industrial worker in 2nd week of its clinical course which responded to oral fluconazole followed by skin grafting since this case scenario in itself is an uncommonly presented and reported event coupled with finding of first ever case with such presentation in this tertiary care institute of Southern Assam. This case is also reported with intention of raising awareness in surgeons for keeping vigil on non-healing burn wounds with empirical antibiotics and about the need of timely pus culture and sensitivity testing to rule out fungal colonization and prevent mortality due to disseminated fungal infection.